Werner Büttner - coincidence in splendour paintings - Falckenberg, Harald 1943-2023; Hofmann, Werner 1928-2013; Kramer, Fritz 1941-2022; Slyce, John 1964-; Weibel, Peter 1944-2023; Williams, Gilda (Black Dog Publishing, 2016)
Exploring the work of Hamburg-based artist Werner Büttner Coincidence in Splendour presents an overview of paintings from the 1980s until the present. back back Büttner is best known for drawing out deeper layers of meaning from daily scenes that, at first glance, may seem banal. He creates surreal assemblages that question our systems of value and contradict our understanding of what elements or images may be brought together. His work confronts social norms with both irony and satire; while retaining a firm understanding of the history of painting, Büttner is constantly testing convention. His large-scale neo-Expressionist and neo-Dadaist works address social issues with a biting and wry humour. In doing so, Büttner uses all genres of painting, including still life, self-portraiture and history painting.
Keywords: Büttner, Werner 1954- / Catalogs; Büttner, Werner -- 1954-; Bildband; Katalog